2017
DOI: 10.1515/ijamh-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes and its relationship with nutritional status: a micro level study on a group of adolescent girls in the city of Howrah, West Bengal

Abstract: The nutritional status of adolescents depends on their eating attitudes and socio-demographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This type of eating habits may lead to nutritional deficiency during adolescence which may have long term consequences such as delayed sexual maturation and lower final adult height [16]. In our neighbor country, studies concluded that disordered eating is more prevalent among overweight adolescent girls compared to their counterparts who were normal weight and underweight [17]. Anthropometric traits of the participants reveal that indices like BMI, WHR and BF% were significantly higher among those participants who have disordered eating attitudes (score ≥ 5) than those with normal eating attitudes (score < 5) [18].…”
Section: Introductionmentioning
confidence: 93%
“…This type of eating habits may lead to nutritional deficiency during adolescence which may have long term consequences such as delayed sexual maturation and lower final adult height [16]. In our neighbor country, studies concluded that disordered eating is more prevalent among overweight adolescent girls compared to their counterparts who were normal weight and underweight [17]. Anthropometric traits of the participants reveal that indices like BMI, WHR and BF% were significantly higher among those participants who have disordered eating attitudes (score ≥ 5) than those with normal eating attitudes (score < 5) [18].…”
Section: Introductionmentioning
confidence: 93%